The Dorsiflexion Range of Motion Screen: A Validation Study - Phillip J Plisky; Garrett S Bullock; Mary Beth Garner; Risa Ricard; Josh Hayden; Bethany Huebner; Kate Schwartzkopf-Phifer; Kyle Kiesel (North American Sports Medicine Institute, 2021)
# Background Limited ankle dorsiflexion (DF) is associated with ankle sprains and other lower extremity injuries. Current ankle measurements can be laborious to perform in an athletic environment. # Purpose The purpose of this study was to determine the reliability and discriminant validity of a novel closed-chain ankle DF ROM test, the standing ankle dorsiflexion screen (SADS). # Study Design Reliability and validity study # Methods Thirty-seven healthy subjects participated in the study. Two raters measured closed-chain ankle DF range of motion (ROM) using a modified lunge position with an electronic inclinometer. Four raters measured ankle DF using the SADS. Reliability was calculated using intraclass correlation coefficients (ICC) and kappa coefficients for the raters using an electronic inclinometer and the SADS scale, respectively. An independent t-test compared the SADS categories of "behind" and "beyond" to the modified lunge test ROM (*p*<0.05). # Results Excellent ICC values (0.95 \[95% CI (0.92,0.97)\]) and high kappa values were observed (0.61-0.81), with high percent agreement (86-94%). There was a significant difference in ankle DF ROM between the nominally scored "behind" and "beyond" categories, regardless of rater or trial analyzed (behind: 41.3° ± 4.7°; beyond: 51.8°± SD 6.1°, *p* <0.001). # Conclusions The SADS was observed to have excellent interrater reliability and high discriminant validity. Furthermore, there was a distinct closed chain ankle DF ROM difference between the "behind" and "beyond" SADS nominal scores. # Clinical Relevance The SADS can be used as a quick and efficient closed chain ankle DF ROM screen. # Level of Evidence 2b